2009
DOI: 10.1111/j.1365-3024.2009.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative imbalance between T regulatory cells and activated T cells in mice with differential morbidity in chronic Schistosoma mansoni infections

Abstract: Chronic (20-week) Schistosoma mansoni infections of CBA/J male mice present as two distinct forms of morbidity. Most mice develop moderate splenomegaly syndrome (MSS) resembling the intestinal form of chronic human schistosomiasis mansoni, while approximately 20% of mice develop hypersplenomegaly syndrome (HSS), more consistent with the severe hepatosplenic form of chronic human schistosomiasis mansoni. Here, we report the relative proportions of natural T regulatory cells (Treg) and activated CD4(+) T cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The central role of Tregs in the control of immune pathology in murine helminth infections is supported by several studies: S. mansoni-infected mice displayed increased liver pathology if Tregs were depleted or Treg expansion was restricted (11,20). Also, the development of severe hypersplenomegaly syndrome in chronic S. mansoni infection correlated to the ratio of Tregs/activated T cells (57). Trichuris muris isolates that induced a more pronounced Treg expansion upon infection displayed prolonged survival within their murine hosts.…”
Section: Discussionmentioning
confidence: 60%
“…The central role of Tregs in the control of immune pathology in murine helminth infections is supported by several studies: S. mansoni-infected mice displayed increased liver pathology if Tregs were depleted or Treg expansion was restricted (11,20). Also, the development of severe hypersplenomegaly syndrome in chronic S. mansoni infection correlated to the ratio of Tregs/activated T cells (57). Trichuris muris isolates that induced a more pronounced Treg expansion upon infection displayed prolonged survival within their murine hosts.…”
Section: Discussionmentioning
confidence: 60%
“…However, the ratios of Treg to Tact in MSS mice are significantly higher than those of HSS mice. It should be noted that the majority of mice develop MSS resembling the intestinal form of chronic human schistosomiasis, whereas only 20% of mice develop HSS that is more consistent with the severe hepatosplenic form of chronic human schistosomiasis mansoni (Watanabe et al 2009). In a study of S. mansoni-infected mice coinfected with murine AIDS (MAIDS), it was found that MAIDS did not influence the hepatic granulomatous reaction to S. mansoni in coinfected mice (Lacroix et al 1998).…”
Section: Use Of Murine Hosts To Study Immunopathologymentioning
confidence: 98%
“…It was reported that innate effectors and regulatory T cells producing IL-10 cooperate to reduce morbidity and prolong survival in schistosomiasis (Hesse et al 2004). Watanabe et al (2009) reported that the proportions of natural T regulatory cells (Treg) and activated CD4 + T cells (Tact) for both splenic and granulomatous cell populations are greater in mice with hypersplenomegaly syndrome (HSS) than those with moderate splenomegaly syndrome (MSS). However, the ratios of Treg to Tact in MSS mice are significantly higher than those of HSS mice.…”
Section: Use Of Murine Hosts To Study Immunopathologymentioning
confidence: 99%
“…For example, expanded and activated Foxp3 + Treg populations down-regulate Th2 responses towards the S. mansoni eggs that engender pathogenic reactions when trapped in tissue vasculature [25,38] and the severity of egg-induced liver pathology is negatively correlated with Foxp3 + Treg numbers [39]. The down-modulation of perioval granuloma 8 weeks post infection is associated with increased Foxp3 + Treg activation [25] and pathology can be alleviated by retroviral transfection of mice with Foxp3 [40] or transfer of infection-associated CD4 + CD25 + Tregs [41].…”
Section: Reviewmentioning
confidence: 99%